The fundamental solutions for the stress intensity factors of modes I, II and III. The axially symmetric problem - Rogowski, Bogdan (Zielona Góra: Uniwersytet Zielonogórski)
The subject of the paper are Green`s functions for the stress intensity factors of modes I, II and III. Green`s functions are defined as a solution to the problem of an elastic, transversely isotropic solid with a penny-shaped or an external crack under general axisymmetric loadings acting along a circumference on the plane parallel to the crack plane. Exact solutions are presented in a closed form for the stress intensity factors under each type of axisymmetric ring forces as fundamental solutions. Numerical examples are employed and conclusions which can be utilized in engineering practice are formulated.
Keywords: cracks; Green`s functions; stress intensity factors; analytical solution; mode I, II and III loading conditions; transversely isotropic